PENGARUH TEKNOLOGI INFORMASI DAN KOMUNIKASI TERHADAP PASAR TENAGA KERJA DAN PERTUMBUHAN EKONOMI DI INDONESIA - Putri, Rahmadani; Idris, Idris (Universitas Negeri Padang, 2020)
Abstract : This study discusses the study and analysis of Information and Communication Technology (ICT) on the Labor and Economic Markets in Indonesia. The data used in this study are panel secondary data from 2012 to 2018 with a sample of 34 provinces in Indonesia. Data obtained from related institutions and then analyzed using the simultaneous equation model (simultaneous equation regression model) with the Indirect Least Square (ILS) method to calculate indirect parameters and calculated using the first with the application of the OLS model through the selection of the CEM, FEM and REM model then continued with classic trials. Partial research results show, Information and communication technology has a significant influence on the Labor Market in Indonesia. Furthermore, simultaneous, Information and Communication Technology and Labor Market have a significant influence on the economic conversation in Indonesia Indonesia. However, partially, Information and Communication Technology has a negative influence on the acceleration of the Economy in Indonesia. Based on the results of this research, the steps in the progress of Information and Communication Technology have become one of the studies for governments that need help, in order to increase insight, use, use, and match for policy makers in developing countries specifically Indonesia so that it can be an appropriate intervention to influence per capita economic growth.Keywords: Information and Communication Technology, Labor, Economic Communication, Solow Model and Simultaneous Equation Model